ANALISIS PERKEMBANGAN SOSIAL REMAJA - Wiantina, Nur Azmi (JIEGC Journal of Islamic Education Guidance and Counselling, 2021)
Human grows and develops in environment. Social environment give lots of impact in shaping lots of life’s aspects, especially social- psychologic aspect. One of adolescent development task which is the hardest is related to social adjustment. Adolescent’s social life marked by the prominence intellectual and emotional’s fungctions. Factors impacting social development such as family, maturity, social economic status, education, and mental capacity